Biologi and Control of White Root Disease of Hevea Rubber Caused by Rigidoporus Lignosus (Klotzsch) Imazeki - Danlag, Expedito Evarola (1987)
White root disease is by far the most serious among the three major root diseases of rubber. Current methods of control of the disease include pre-planting control procedures, such as mechanical or hand clearing, sulphur amendment, use of covers and intercrops: post-planting control procedures, i.e. disease detection, treatnent with collar protectant dressing: the use of isolation trenches in mature rubber: and more recently the application of calixin emulsion as soil drench. High costs of labour and chemicals, however, made these methods rather expensive, not to mention the serious hazard chemicals pose to the environment. This study explored same possible methods of white root disease control which minimize, if not completely avoid, dependency on chemicals. Such methods as introduction of antagonists, application of chemicals at minimal rate and addition of organic matter supplement applied either individually or in combination with each other were included in the study. Results demonstrated that chemically assisted biological control against white root disease could be achieved with combined application of the different treatments It was also evident that the inclusion of antagonists and caw manure in the treatments further enhanced increase of population of the mycoflora. Fifty percent of the treatments with total population of mycoflora significantly higher than that of the control included both antagonists and caw manure.